Anthropogenic influences on the distribution of a Vulnerable coniferous forest specialist: habitat selection by the Siberian musk deer Moschus moschiferus. Issue 1 (11th May 2017) - Slaght, Jonathan C.; Milakovsky, Brian; Maksimova, Dariya A.; Seryodkin, Ivan V.; Zaitsev, Vitaliy A.; Panichev, Alexander M.; Miquelle, Dale G.
Abstract: The Siberian musk deer Moschus moschiferus, categorized as Vulnerable on the IUCN Red List, is a small ungulate associated with coniferous forests of East Asia. In Russia the species is hunted both legally and illegally for the commercially valuable musk gland in males. Steep population declines recorded in recent decades have been generally attributed to intensive illegal hunting, but the decline has coincided with increased logging activity and the concomitant expansion of logging roads. We conducted an occupancy analysis in Primorskii Krai, Russia, to elucidate the relative importance of environmental, ecological and anthropogenic features associated with the presence of musk deer. The top model contained covariates related to the abundance of bearded lichen Usnea spp., the distance to a main road and the distance to logging sites, suggesting that both intensive hunting of musk deer (associated with greater accessibility via roads) and logging of habitat are influencing the occurrence of this species. We propose several management actions to limit the negative influence of logging and logging roads on musk deer in Russia, including encouraging logging companies to set aside high conservation value forests (to retain intact forests) and to close logging roads post-harvest (to reduce access by poachers).